(untitled) (Archives of Criminology, 1986)
The aims of the present study have been: 1) to ascertain the actual conditions of the courts’ decisions applying penalties and other measures towards multiple recidivists; 2) to determine the present penal policy towards this category of convicted persons; 3) to compare this policy with the assumptions included in the Penal Code in force. Punishment imposed upon multiple recidivists is regulated by the provisions of Art. 60, para. 2 and 3 Art. 61 of the Penal Code. Their formulation is as follows: on a perpetrator sentenced twice in the conditions specified in para. 1 (special basic recidivism), who has served altogether at leat one year of deprivation of liberty and in the period of 5 years after the serving of the last penalty commits again an intentional offence with the purpose of obtaining a material benefit or of a hooligan character, similar to at least one of the previously committed offencęs, the court shall impose a penalty within the limits of from three times the lowest sanction, but not less than 2 years, up to the highest statutory sanction increased by one half, and if the highest statutory sanction is not higher than 3 years: up to 5 years deprivation of liberty. The increase of the lowest statutory sanction provided in para. 1 or 2 shall not apply, when the offence is a serious offence; in this case the court shall consider the commission of the offence in the conditions specified in para 1 or 2 as a circumstance increasing the penalty. In particularly justified cases when even the lowest penalty imposed on the basis of Art. 60. paras 1 or 2 would be incommeasurably Severe by reason of the motives for the action of the perpetrator, his traits and personal conditions as well as his way of life before the commission and his behaviour after the perpetration of the offence, the court when imposing the penalty may refrain from applying the rules specified in Art. 60. paras 1 or 2; in these cases the court shall take into consideration the commission of the offence in the conditions specified in Art. 60, para 1or 2 as circumstances influencing increasing the penalty. With regard to a perpetrator sentenced in the conditions specified in Art. 60, para. 2 he court shall adjudge protective supervision; if adjudging this supervision is not sufficient to prevent recidivism, the court shall adjudge .the commitment of the sentenced person to a social readaptation centre. (Art. 62, para. 2). The present work has been based on the author’s own research and to a minimum extent only on the analysis of the national statistical data. The point of departure for the study of the actual conditions of the courts decisions were the conditions specified in the Penal Code now in force. The conditions specified in Art. 61 of the Penal Code and related to the offender only have been assumed to form the ratio legis of special recidivism in the Polish penal legislation. If, however, when aplying this provision, the courts prefer the conditions related to the most recent act of the offender, this mignt be an indication of their different attitude towards the aim of punishment in the case of the discussed category of offenders. The existence of such divergences between the conditions of application of Art 61 of the Penal Code as included in the law on the one hand, and those applied by the courts on the other hand has been one of the hypotheses verified in the present study. The study has been based on the examination of court records. All the accessible records of criminal cases (230) have been included in it, in which Sentences were passed with regard to multiple recidivists (under Art 60. para. 2 and Art. 61 in connection with Art. 60, para. 2 of the Penal Code) in the District Court of the city of Poznań in the years 1975-1981. The question arised whether this could be treated as an equivalent to a random sample of the national population of convicted multiple recidivists. As shown by a comparison of distributions in question are highly convergent. A questionnaire to investigate the ourt records consisted of 41 questions concerning the convicted recidivist, his previous offences and criminal record, his last offence and the content of the last sentence. The impact of a number of variables on the application of Art. 61 of the Penal Code, on the length of the prison sentence and on the decision of commitment to a social readaptation centre has been analysed in succession. Conclusions from the study are as follows: 1. In the application of Art.61 of the Penal Code ,the predominating part is played by the conditions connected with the degree of socil danger of the act and with its legal label. The conditions connected with the person of the perpetrator seem to have a much smaller effect. The reason of this state of affairs may be seeked in the fact that the court is obligated by Art. 60, para.2 of the Penal Code to impose long-term penalties of deprivation or liberty regardless of the degree of social danger (seriousness) of the offence which may be trivial in particular cases. Therefore, it is not to be wondered at that in these cases the courts apply Art. 61 of the Penal Code so as to impose a lower or more lenient penalty in order to make it commeasurable with the offence. The following conditions have been found to exert the greatest influence on the length of sentences to deprivation of liberty under Art. 60, para. 2: firstly, the legal appraisal of the offence and the related content of the instructions for meting out punishment specified in Art. 60, para. 2 of the Penal Code, and secondly, the degree of social danger of the offence. The character of the offence and the appraisal of its social danger influence the sentence too, including the type of penalty, when Art. 61 of the Penal Code is applied by the court. This is probably a further result of following the same conditions already when deciding on the application of Art. 61 of the Penal Code. When adjudging the commitment of convicted persons to a social readaptation centre, the courst were guided by the conditions connected with intense symptoms of demoralization of these persons and with a previous application of various penal measures towards them; thus the conditions were formally the same as those to be found in the Penal Code. At the same time, conditions connected with the recently committed offence were left out of account here. One should be particularly careful when interpreting the findings in this case aS the decisions in question may be conditioned by the courts’ various attitudes towards the practical functioning of the centers, and by different purposes of their adjudgement in definite cases. The length of the perod for which commitment to a social readaptation centre was adjudged has appeared to increase with the length of the sentence to deprivation of libety. Admittedly, outright conclusions as to the need for amendments of the provisions of the Penal Code in its part concerning recidivists do not follow immediately from the findings of the present study. These findings have. however, demonstrated the degree to which the instructions for meting out, punishment specified in Art. 60, para. 2 of the Penal Code sever the relation between the offence and punishment, as well as the fact that the corrective function of punishment imposed upon multiple recidivists - officially assumed by the legislator-has a fictious character in practice. In consequence, Art. 61 of the Penal Code is used in discord with its purpose; it is applied to adjust the adjudicated punishment to the seriousness of the offence committed.